2009
DOI: 10.1055/s-0029-1211099
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Bone Turnover in Young Adults

Abstract: Physical activity has been suggested as one of the determinants of bone turnover and to prevent the involutional age related bone loss. However, the degree to which physical exercise is necessary to induce changes in bone turnover and calciotropic hormones have been widely discussed (Williams et al., 1984; Cook et al., 1987; Smith et al., 1985). The aim of this study was to examine the rate of bone formation measured by osteocalcin in 56 healthy volunteers before and after 4 and 8 weeks of physical exercise (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…On the other hand, Franck et al17 reported that weight-bearing exercise training done 2-3 times a week in young subjects led to a significant reduction in OC within 4 weeks, followed by recovery to the previous level in 8 weeks. It was suggested that such adaptation to exercise was due to an increase in PTH release and a decrease in OC production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Franck et al17 reported that weight-bearing exercise training done 2-3 times a week in young subjects led to a significant reduction in OC within 4 weeks, followed by recovery to the previous level in 8 weeks. It was suggested that such adaptation to exercise was due to an increase in PTH release and a decrease in OC production.…”
Section: Discussionmentioning
confidence: 99%
“…Frank et al17 reported that OC significantly decreased in 4 weeks followed by recovery to pre-exercise concentrations after 8 weeks of exercise intervention using pre-exercise, 4 week, and 8 week OC measurements. In addition, calcium decreased in 4 weeks and then stabilized at the pre-exercise concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of BMD is inadequate to detect acute changes in bone metabolism after physical activity because changes in bone mass usually occur at a slow rate. The skeletal response to exercise can be measured using blood markers to estimate the bone remodeling rate by comparing the resorption markers to formation markers [23]. Also, a study by Chien et al [24] demonstrated that a 24-week program of aerobic high-impact exercise resulted in significant improvements in BMD of the femoral neck in Chinese postmenopausal women.…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
“…The relatively new development of assays for circulating biochemical markers of bone turnover now allowing us to gain greater mechanistic insight into the effects of factors like exercise and maturation on bone development. [11][12][13][14] Although the majority of newly synthesized osteocalcin is deposited into bone matrix, a small amount can be detected in blood, and it is this characteristic that has led to its current clinical use as a specific index of osteoblastic activity. It is the most abundant and most widely studied of the non-collagenous proteins in bone.…”
Section: Introductionmentioning
confidence: 99%